ADOPSI VISUAL FESYEN BIKERS - Dewi Widowati (Jurnal Da Moda, 2019)
Bikers style, also known as 'motorcycle outlaw', is one of the street style sub-styles that appeared in 1947-1950 in Southern California. This style which is identical with rock n roll music is a combination of masculine image and freedom. The fashion items of this style consist of captain hat, motorcycle jacket, white shirt, gloves (black leather), brown leather belt with standard buckles, branded jeans, and engineer boots. Along with the development of the era and the process of acculturation brought bikers style at the time, culture, and place of Indonesia has made the original character shifted with the current trend of development, especially among young people in Bandung. The formulation of the problem in this study is about how the process of visual adoption and shift in bikers style that occurred in Bandung, and the extent of its influence on the style of dress among young people in Bandung. This research uses a qualitative / analytic descriptive study method, with media studies including object analysis based on the theory of fashion shift (Rouse) and the basis of the type name style (Takamura). The findings in this study are a shift in how to use / solid match on the bikers style that developed in Bandung due to cultural, economic, and saturation factors among young people of Bandung to distributions / clothing that have the same concept / seem flat & mainstream.